Pemberdayaan Lansia Mengelola Diabetes Melitus melalui Edukasi dan Akupresur di Posyandu Mojosongo - Sumanto; Nurmila Mutiah (Rena Cipta Mandiri, 2026)
Diabetes mellitus is a non-communicable disease whose prevalence is rising among older adults and requires long-term management through pharmacological and non-pharmacological approaches. Limited health literacy, suboptimal adoption of healthy behaviors, and the limited capacity of community health volunteers (kader) in chronic-disease assistance were the main problems faced by Yasadharma Elderly Integrated Health Post (Posyandu Lansia), RW 18 Rinjani Mojosongo, Surakarta. This community service program aimed to improve older adults' knowledge, skills, and self-management of diabetes mellitus through health education and acupressure training as a complementary therapy. The program was conducted from 7 to 23 October 2025, involving 49 older adults through educational and participatory approaches consisting of interactive lectures, discussions, demonstrations, hands-on practice, and mentoring by cadres. Evaluation was carried out qualitatively and descriptively through observation, brief interviews, and participant reflection. The results indicated improved participant understanding of diabetes mellitus and healthy lifestyles, along with the ability to independently perform acupressure at ST36 (Zusanli) and SP6 (Sanyinjiao). Cadres also showed enhanced mentoring competence. Evaluation was descriptive, without clinical measurement or statistical testing. The program has the potential to support community-based diabetes management by strengthening the promotive and preventive role of elderly health posts.